Key constraints and opportunities for pastoral development projects engineering and rangeland governance in South Tunisia - Frija, Aymen; Sghaier, Mariem; Sghaier, Mongi; Dhehibi, Boubaker; Fetoui, Mondher (Centre International de Hautes Etudes Agronomiques Méditerranéennes, 2021)
Pastoral development projects engineering in Tunisia has encountered several problems due to the complexity of rangeland resources, territories, societies, and institutional settings. The aim of this paper is to depict some of the current constraints and opportunities faced by three pastoral investment project management units (PMU) in South Tunisia, while characterizing the wider impact of these projects on rangeland governance. We assessed three pastoral development projects in South Tunisia to appreciate their compliance with principle of enhanced development projects engineering including: i) relevance and coherence of the project; ii) effectiveness; iii) efficiency of implementation; and iv) impact orientation and sustainability. The data was gathered using an online questionnaire and focus group discussions with leaders of the three project PMUs. Results emerging from this research show that it is highly important to include infrastructure investments of the projects into a broader perspective of pastoral economic and territorial development. It is further important for pastoral development projects to invest in building enhanced social capital, networks and norms. The impact of the later investments will not be immediate but contributes to building long term resilience and sustainability.